Biblijne owoce Ducha Świętego (Ga 5, 22-23) na drodze do dojrzałej wiary w katechezie - Kopiczko, Tomasz (Verbum Vitae, 2020)
The article is a theological and catechetical analysis of the fruits of the Holy Spirit (Gal 5: 22-23) on the path to shaping mature faith via the catechetical process. The analytical process employed in the article was divided into three points: the fruit of the Holy Spirit, mature faith, and mature man. The analysis of biblical texts and catechetical documents allows us to draw three conclusions. First of all, it is the Holy Spirit who is the giver of grace and the source that gives rise to faith. Secondly, the virtues that are mentioned by Saint Paul in the Letter to the Galatians as the fruit of the Spirit acting in man should be considered the features of a mature faith. Third, the task of catechesis is to help the believer to discover the richness of the Holy Spirit's gifts and their implementation.